(untitled) (Revista Brasileira Multidisciplinar, 2026)
Oropharyngeal carcinoma is a type of neoplasia that affects the base of the tongue, the tonsils and the soft palate, and is associated with smoking and alcohol consumption, as well as infection by the Human Papillomavirus (HPV). This study investigated the relationship between oropharyngeal carcinoma in the state of São Paulo and infection with the Human Papillomavirus (HPV) as an associated risk factor. Data from 2014 from the Population-Based Cancer Registries (RCBP) of five regions of the state were analyzed. The analysis identified 128 cases in masculine sex, with a higher incidence in the age group of 55 to 59 years, and 39 cases in women. Although statistical tests (p > 0.05) revealed no significant differences between the groups, descriptive analysis indicated a higher prevalence in men, possibly associated with an increase in the number of sexual partners and the practice of oral sex. Infection with HPV, especially types 16 and 18, was highlighted as a relevant factor in the development of this type of cancer, surpassing traditional risk factors such as smoking and alcohol consumption. Previous studies, including international investigations, also corroborate the increased incidence of cancers associated with HPV, indicating vaccination as an effective preventive strategy. Based on the findings, it is concluded that oropharyngeal cancer in men is closely related to HPV infection, reinforcing the importance of educational campaigns, public vaccination policies and awareness about safe sexual practices as measures to reduce the incidence of this neoplasm.